Assessing the Accuracy of Diagnostic Tests. Issue 3 (25th July 2018) - Li, Fangyu; He, Hua
Abstract : Gold standard tests are usually used for diagnosis of a disease, but the gold standard tests may not be always available or cannot be administrated due to many reasons such as cost, availability, ethical issues etc. In such cases, some instruments or screening tools can be used to diagnose the disease. However, before the screening tools can be applied, it is crucial to evaluate the accuracy of these screening tools compared to the gold standard tests. In this assay, we will discuss how to assess the accuracy of a diagnostic test through an example using R program.